Stable resistance in gram (Cieer arietinum) against Race 2 of Fusarium oxysporum f sp cieed - GURHA, S N; VISHWADHAR, VISHWADHAR; NAIMUDDIN, NAIMUDDIN; SINGH, R A (The Indian Journal of Agricultural Sciences, 2014)
A total of 320 genotypes in 1994-95 and 370 in 1995-96 were screened against Race 2 of Fusarium oxysporum f sp cieed (Padwick) Snyd. & Hans. In confirmatory test of the gram (Cieer arietinum L.) genotypes found resistant or moderately resistant, 9 genotypes, viz ’BG 209’, ’PO 8602-10-12’, ’ICCV 93217’, ’C 235’, ’BO 1043’, ’PBG 1’, ’GL 930 11, ’GL 90236’ and ’H 92-71’ exhibited stable resistance. However, 26 genotypes were found to have stable moderate resistance with wilt incidence between 10% and 20%. Seven genotypes showed stable tolerance against wilt disease.